Mentoring disadvantaged youths during school-to-work transition: evidence from Germany - Bernhard Boockmann; Sebastian Nielen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In the German school and vocational education systems, there is a wide range of support measures during school-to-work transition. We analyze a novel program providing mentoring to low-achieving school leavers as a bridge between different stages and different institutional systems in secondary and post-secondary education. Using high-quality survey and administrative data and propensity score matching, we find some positive effects on the probability of transiting into the dual vocational education system in the intermediate run. Higher program intensity leads to larger treatment effects. Contrary to the goals of the program, however, there is only weak evidence that it accelerates transitions into vocational training immediately after leaving school.
Keywords: J24; I21; I28; 330